Morphophysiological Response of Edamame Soybean to Arbuscular Mycorrhizal Fungi (AMF) and Bioactive Compost Charcoal in Tidal Swamp Land - Shinta Rosalina; Iwan Sasli; Tatang Abdurrahman (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Edamame soybean cultivation in Indonesia has great potential due to its high nutritional value and increasing market demand. However, the current productivity remains low, thereby hindering commercial development. This study aimed to enhance the growth and yield of edamame soybean plants through the application of Arbuscular Mycorrhizal Fungi (AMF) and bioactive compost charcoal on tidal swamp lands. The research was conducted using a split-plot design consisting of two AMF treatments and four levels of bioactive compost charcoal. The results indicated that the combination of AMF and bioactive compost charcoal significantly increased various growth parameters and yield. Although a dose of 10 ton/ha produced vegetative growth equivalent to that achieved by applying 15 ton/ha corn stalk compost, a dose of 15 ton/ha resulted in more optimal harvest outcomes, with pod numbers reaching 43.22 units per plant, pod weight of 91.67 g per plant, and pod weight of 1.545 kg per plot. Furthermore, the treatment also increased the percentage of AMF colonization in roots as well as phosphorus uptake, which contributed to the enhancement of plant productivity.